2020
DOI: 10.1111/jgh.15361
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of Fusobacterium nucleatum in the progression of colorectal cancer

Abstract: Background and Aim: Fusobacterium nucleatum (Fn) is involved in colorectal cancer (CRC) growth and is a biomarker for patient prognosis and management. However, the ecology of Fn in CRC and the distribution of intratumoral Fn are unknown. Methods: We evaluated Fn and the status of KRAS and BRAF in 200 colorectal neoplasms (118 adenomas and 82 cancers) and 149 matched adjacent normal mucosas. The differentiation status between "surface" and "deep" areas of cancer tissue and matched normal mucosa were analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…In our study, the presence of F. nucleatum was significant at tumour size > 4 cm ( P = 0.053). Tumour size and TNM stage III/IV have also been associated with F. nucleatum in other studies [ 67 ]. In addition to FadA mechanisms, TLR4 activation by F. nucleatum ’ LPS can plausible lead to the activation of Myd88 and NF-κB, which leads to oncogenic overexpression of miR21, resulting in dysregulated growth and infiltration of tumour tissue.…”
Section: Discussionmentioning
confidence: 71%
“…In our study, the presence of F. nucleatum was significant at tumour size > 4 cm ( P = 0.053). Tumour size and TNM stage III/IV have also been associated with F. nucleatum in other studies [ 67 ]. In addition to FadA mechanisms, TLR4 activation by F. nucleatum ’ LPS can plausible lead to the activation of Myd88 and NF-κB, which leads to oncogenic overexpression of miR21, resulting in dysregulated growth and infiltration of tumour tissue.…”
Section: Discussionmentioning
confidence: 71%
“…It has also been reported that Fn may encode virulence factors, such as FadA, Fap2, and MORN2 proteins, to induce CRC development ( Ranjbar et al., 2021 ). Consistent with these lines of experimental evidence, clinical studies demonstrate that the abundance of Fn in CRC tissues is significantly increased compared with the adjacent normal tissues, and a high prevalence of Fn is associated with advanced stage, metastasis, recurrence, and short OS of CRC patients ( Eisele et al., 2021 ; Mima et al., 2016 ; Serna et al., 2020 ; Yamamoto et al., 2021 ).Therefore, Fn, as a potential oncobacterium, may be helpful for the early detection and prognostic prediction of CRC.…”
Section: Introductionmentioning
confidence: 57%
“…The importance of Fn in colorectal tumors has recently been revealed. We have previously reported the presence of Fn in colorectal adenoma and colorectal cancer ( 20 ), and we hypothesized that Fn might play an important role in SNADETs as well. The incidence of Fn in duodenal adenoma, early-stage duodenal adenocarcinoma, and advanced-stage duodenal adenocarcinoma was 10.9%, 24.4%, and 25.0%, respectively ( P = 0.10).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of Fn DNA in tissues was measured by qPCR. Custom-made primer/probe sets were used to amplify Fn and the reference human gene solute carrier organic anion transporter family number 2A1 ( SLCO2A1 ), as previously described ( 20 ). The primer and probe sequences are summarized in Supplemental Table 1 (Supplementary Digital Content 1, http://links.lww.com/CTG/A718 ).…”
Section: Methodsmentioning
confidence: 99%